Cost-Effectiveness of Physical Therapy Only and of Usual Care for Various Health Conditions: Systematic Review. Issue 6 (1st June 2016) - Bürge, Elisabeth; Monnin, Dominique; Berchtold, André; Allet, Lara
Abstract : Background: Given continually rising health care costs, interventions of health care providers should be cost-effective. Purpose: This review aimed to summarize current cost-effectiveness of physical therapy. Specific aims were: (1) to analyze cost-effectiveness of physical therapy only compared with usual care only, (2) to analyze cost-effectiveness of physical therapy added to usual care compared with usual care only, and (3) to specify in which health conditions physical therapy only or physical therapy added to usual care was cost-effective. Data Sources: Topic-related systematic reviews were searched in MEDLINE, CINAHL, PEDro, and Cochrane Library and manually. Study Selection: Studies published between 1998 and 2014 that investigated the cost-effectiveness of interventions carried out by physical therapists were reviewed. The methodological quality was assessed with the Cochrane risk of bias assessment for intervention studies and with the Quality of Health Economic Analyses Scale. Data Extraction: Effectiveness and cost data for calculating incremental cost-effectiveness ratios (ICERs) and the original authors' conclusions were extracted. Data Synthesis: The 18 included studies presented low risk of bias and contained 8 comparisons of physical therapy only with usual care only and 11 comparisons of physical therapy added to usual care with usual care only. Based on ICERs, physical therapy only or added to usual care was cost-effective in 9 out of the 19 comparisons and in 10 comparisons according to the original authors' conclusions. Conclusion: Physical therapy only or added to usual care implies improved health in almost all studies. The cost-effectiveness of such interventions was demonstrated in half of the studies. This result might have been influenced by the fact that different definitions of the notion of "cost-effectiveness" exist.